Asthma is more prevalent in elite swimming adolescents despite better mental and physical health - Romberg, K.; Tufvesson, E.; Bjermer, L. (Scandinavian Journal of Medicine & Science in Sports, 2012)
An increased risk of developing asthma has been reported among swimmers exposed to chloramine in pool arenas. The aim of the present study was to compare the prevalence of asthma and respiratory symptoms among elite aspiring swimmers compared with age-matched controls with different degrees of physical activity. We also aimed to relate these findings to mental and psychosocial factors. One hundred and one elite swimmers and 1628 age-matched controls answered a questionnaire containing questions about respiratory symptoms, lifestyle factors, mental and physical well-being. The controls were divided into three different groups according to the degree of physical activity, no physical activity, recreational training and elite training. Swimmers reported significantly more asthma symptoms, with 36.6% having physician-diagnosed asthma, compared with 16.2% among the controls. Use of regular medication was more common (14.9% vs 8.0%) and more swimmers reported an exacerbation of their asthma during the previous 12 months (16.8%) vs (5.8%) for the controls. Despite an increased prevalence of asthma symptoms, the swimmers reported best physical performance and best mental and physical well-being. They also had a healthier lifestyle without smoking and low alcohol consumption.